'Nobody teases good girls': A qualitative study on perceptions of sexual harassment among young men in a slum of Mumbai. Issue 9 (2nd September 2018) - Zietz, Susannah; Das, Madhumita
ABSTRACT: Young adulthood is a key period in which gender norms are solidified. As a result, young women are particularly vulnerable to gender-based violence. In Delhi, over 90% of women have ever experienced sexual violence in public spaces. Sexual harassment of girls and women in public spaces is commonly named 'eve teasing' in India. Experience of sexual harassment in public spaces has been found to be associated with restricted mobility, interrupted education, and early age at marriage. Little is known about men's perspectives on eve teasing and how they believe it affects women and girls. This study fills that gap through qualitative research to explore the attitudes and perceptions of adolescent boys and young men on this topic. Ten focus group discussions were conducted in two slum communities in Mumbai. Coding and thematic analysis were performed. We identified themes of acceptance of harassment, weak sanctions, traditional gender norms supportive of harassment, and ideologies of male sexual entitlement. Many of the perceived risk and protective factors for sexual harassment in public spaces are operationalised at the community level. Community mobilisation is necessary in designing interventions focused on the primary and secondary prevention of sexual harassment.